2013
DOI: 10.1016/j.urology.2013.01.078
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Intermittent Androgen Deprivation Therapy vs Conventional Continuous Androgen Deprivation Therapy for Advanced Prostate Cancer: A Meta-analysis

Abstract: OBJECTIVE To compare the efficacy of intermittent androgen deprivation therapy (IADT) vs continuous androgen deprivation therapy (CADT) for the treatment of advanced prostate cancer; we performed a meta-analysis of randomized controlled trials (RCTs), assessing the risks of disease progression, all-cause, and disease-specific mortality. MATERIALS AND METHODS We conducted a systematic search of several bibliographic systems to identify all RCTs of IADT in men with newly diagnosed metastatic or biochemical onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 22 publications
0
41
0
Order By: Relevance
“…30,31 The results show a small and non-significant decrease in cause-specific mortality, overall mortality, and disease progression with the use of IHT, but a significant reduction in the emergence of hot-flushes. The authors of that meta-analysis conclude that IHT is a reasonable option for well-informed patients who want to avoid these side-effects.…”
Section: Continuous or Intermittent Adtmentioning
confidence: 95%
“…30,31 The results show a small and non-significant decrease in cause-specific mortality, overall mortality, and disease progression with the use of IHT, but a significant reduction in the emergence of hot-flushes. The authors of that meta-analysis conclude that IHT is a reasonable option for well-informed patients who want to avoid these side-effects.…”
Section: Continuous or Intermittent Adtmentioning
confidence: 95%
“…During the management of advanced prostate cancer, previous studies have demonstrated that IADT is at least as effective as continuous treatment with regard to disease progression and overall survival (12)(13)(14). However, IADT should be considered as an alternative therapeutic approach to CADT, accounting for the caveats and cautions suggested by meta-analysis of eight randomized controlled trials of intermittent vs. continuous ADT (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…However, IADT should be considered as an alternative therapeutic approach to CADT, accounting for the caveats and cautions suggested by meta-analysis of eight randomized controlled trials of intermittent vs. continuous ADT (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We shall refer to this cancer cell type as having strategy T + . To target these cancer cells' need for testosterone, androgen deprivation therapy (ADT) stops normal production of testosterone in the patient -a treatment termed "chemical castration" (Yao et al, 2008;Hussain et al, 2013;Tsai et al, 2013). Virtually all patients initially respond to ADT.…”
Section: Background: Metastatic Castrate-resistant Prostate Cancermentioning
confidence: 99%